Proceedings of the Twenty-Eighth International Joint Conference on Artificial Intelligence 2019
DOI: 10.24963/ijcai.2019/614
|View full text |Cite
|
Sign up to set email alerts
|

AddGraph: Anomaly Detection in Dynamic Graph Using Attention-based Temporal GCN

Abstract: Anomaly detection in dynamic graphs becomes very critical in many different application scenarios, e.g., recommender systems, while it also raises huge challenges due to the high flexible nature of anomaly and lack of sufficient labelled data. It is better to learn the anomaly patterns by considering all possible features including the structural, content and temporal features, rather than utilizing heuristic rules over the partial features. In this paper, we propose AddGraph, a general end-to-end anomalous ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(118 citation statements)
references
References 4 publications
0
118
0
Order By: Relevance
“…FGSS has ideal graphical scales over researches [43] and [39], hence it could recognize anomalous samples in HD spaces. Moreover, the author [85] proposed AddGraph to distinguish (8) SOD R(p) (p) = distance(Pointo, HyperPlan(R(p)))∕v R(p) 1 , the anomalous users that create counterfeit information to accomplish the potential gain. The GAD model detects the long-term and short-term anomalous patterns of fake data using dynamic graphs.…”
Section: High Dimensional Sub-space Based Techniquesmentioning
confidence: 99%
“…FGSS has ideal graphical scales over researches [43] and [39], hence it could recognize anomalous samples in HD spaces. Moreover, the author [85] proposed AddGraph to distinguish (8) SOD R(p) (p) = distance(Pointo, HyperPlan(R(p)))∕v R(p) 1 , the anomalous users that create counterfeit information to accomplish the potential gain. The GAD model detects the long-term and short-term anomalous patterns of fake data using dynamic graphs.…”
Section: High Dimensional Sub-space Based Techniquesmentioning
confidence: 99%
“…Dynamic graph anomaly detection was performed in [62], where an Attentionbased temporal Graph Convolutional Network (GCN) model was developed. In this study, anomalous edges of the graph were identified utilizing temporal features as the long and short term patterns occurring within dynamic graphs.…”
Section: Graph-based Approachesmentioning
confidence: 99%
“…We use an adjacency matrix A t ∈ R n×n to represent edges in E t where n = |V t |. Similar to [24,27,47,50], the number of nodes in the graph is assumed to be constant across all timestamps (thus maintaining the shape of the adjacency matrix A t ). However, our method is also applicable to real world networks where the number of active nodes fluctuates from one snapshot to another.…”
Section: Problem Definition 31 Dynamic Graphmentioning
confidence: 99%